Improving Phosphorus use Efficiency with Polymer Technology - Sanders, J.L.; Murphy, L.S.; Noble, Anne; Melgar, R.J.; Perkins, James (Procedia engineering, 2012)
The soil microenvironment surrounding a P fertilizer granule or within a fluid P fertilizer band is subject to a series of primary and secondary solution reactions which substantially impact P availability to plants. Influencing or slowing these reactions is a means of improving applied P use efficiency, improving yields and profitability with positive implications for environmental concerns. It is well recognized that even under the best conditions, only 5 to 25% of fertilizer P is taken up by the crop during the first growing season. Thus, the historical problem with the soil chemistry of P fertilizers has been the lack of availability due to soil fixation reactions. The patented Avail ̈ polymer technology positively affects P use efficiency by limiting soil solution reactions which fix P thus extending availability of applied fertilizer P and ultimately providing economical and profitable benefits for growers, manufacturers and distributors. The functionality of the polymer is predicated on the polymer's high effective charge density. Extensive studies with Avail̈ have been conducted since 1999 with investigations in the United States, Canada, United Kingdom, Argentina, The Philippines and many other countries. A wide number of crop species and soil conditions have been involved in these investigations with both solid and fluid P sources. Results of many of these investigations are reported in this paper.